Influence of socio-philosophical and spiritual values on the formation of social orientation and physical health specialists the sphere of physical culture and sports - V.V. Feuerman (Physical Education of Students)
Purpose: to study the relationship of social and philosophical values and level of social and individual substructures due to her physical health. Formation worldview and the highest level of general culture of students specialty "Physical Education". Material: participated in the study students of the Faculty of Physical Education and Sports, totaling 16 people, specializing in basketball. Results: shown in percentage desired relationship (high level "Socio-mediated substructure of personality" - a low percentage of injury). Installed directly proportional relationship of socio-philosophical and spiritual values, the level of social orientation of the individual and the level of general culture of the person who plays sports with her physical health and the presence or absence of injury during exercise. Conclusions: problem of the relationship of socio-philosophical and spiritual values of health, physical development and motor preparedness person becomes relevant the last decade. Search for the missing component - "Advantages of the Spirit", continue to increase in order to achieve higher objectives Sports - Formation of a harmoniously developed person.